2019
DOI: 10.3390/jcm8122218
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Arterial Lactate Levels at Weaning from Postcardiotomy Venoarterial Extracorporeal Membrane Oxygenation

Abstract: Background: The outcome after weaning from postcardiotomy venoarterial extracorporeal membrane oxygenation (VA-ECMO) is poor. In this study, we investigated the prognostic impact of arterial lactate levels at the time of weaning from postcardiotomy VA. Methods: This analysis included 338 patients from the multicenter PC-ECMO registry with available data on arterial lactate levels at weaning from VA-ECMO. Results: Arterial lactate levels at weaning from VA-ECMO (adjusted OR 1.426, 95%CI 1.157-1.758) was an inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 13 publications
3
16
0
Order By: Relevance
“…This is consistent with a previous study that reported a MAP of 80 (IQR, 68‐91) mmHg in 49 successfully weaned patients 6 . Several studies have shown a close association between high pre‐ECMO lactate level and mortality in patients receiving ECMO for cardiac causes 13‐15 ; however, only one study has reported the prognostic value of arterial lactate at time of weaning from ECMO 16 . Biancari et al observed that a cut‐off level of arterial blood lactate ≥ 1.6 mmol/L at weaning was predictive of hospital mortality.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with a previous study that reported a MAP of 80 (IQR, 68‐91) mmHg in 49 successfully weaned patients 6 . Several studies have shown a close association between high pre‐ECMO lactate level and mortality in patients receiving ECMO for cardiac causes 13‐15 ; however, only one study has reported the prognostic value of arterial lactate at time of weaning from ECMO 16 . Biancari et al observed that a cut‐off level of arterial blood lactate ≥ 1.6 mmol/L at weaning was predictive of hospital mortality.…”
Section: Discussionsupporting
confidence: 91%
“…The cumulative survival for patients who met the weaning criteria and patients failing to meet criteria at first attempt was 85% (95% CI, 64%-94%) and 17% (95% CI, 3%-41%), respectively, (P < .001) however, only one study has reported the prognostic value of arterial lactate at time of weaning from ECMO. 16 Biancari et al observed that a cut-off level of arterial blood lactate ≥ 1.6 mmol/L at weaning was predictive of hospital mortality. In our population, there was no significant difference in arterial lactate level and pH at the time of weaning between patients fulfilling the weaning criteria and patients failing the criteria.…”
Section: Ta B L E 2 Outcome Variables F I G U R Ementioning
confidence: 99%
“…In a recent large multi-centric study of post-cardiotomy cardiac failure treated with VA-ECMO, lactate level >1.6 mmol/L at weaning was predictive of in-hospital mortality. 24 However, weaning failure remains higher than 50% even when these criteria are fulfilled and is associated with an increase in overall mortality. [7][8] Indeed, weaning failure is associated with the use of another form of temporary mechanical circulatory support, weaning failure related shock requiring the use of high dose vasopressors and inotropes, increased arrhythmia, a greater myocardial energy imbalance, excessive peripheral vasoconstriction and subsequent organ hypo-perfusion, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…High lactate levels at weaning were predictive of in-hospital mortality in postcardiotomy patients treated with VA-ECMO. 24 VIS was used in order to homogenize data concerning vasopressor or inotrope use after VA-ECMO removal, and value ≤10 was used according to previous studies. 31 We decided to administer levosimendan before VA-ECMO weaning.…”
Section: Discussionmentioning
confidence: 99%
“…3 Furthermore, when assessing lactate prior to weaning off VA-ECMO, post-cardiotomy patients with lactate ⩾1.4 mmol/L had significantly higher risk of hospital mortality compared to patients with lower lactate levels. 4…”
Section: Introductionmentioning
confidence: 99%